2013
DOI: 10.1523/jneurosci.3560-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Calpains, Cleaved Mini-DysferlinC72, and L-Type Channels Underpin Calcium-Dependent Muscle Membrane Repair

Abstract: Dysferlin is proposed as a key mediator of calcium-dependent muscle membrane repair, although its precise role has remained elusive. Dysferlin interacts with a new membrane repair protein, mitsugumin 53 (MG53), an E3 ubiquitin ligase that shows rapid recruitment to injury sites. Using a novel ballistics assay in primary human myotubes, we show it is not full-length dysferlin recruited to sites of membrane injury but an injury-specific calpain-cleavage product, mini-dysferlin C72 . Mini-dysferlin C72 -rich vesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
156
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(162 citation statements)
references
References 32 publications
5
156
1
Order By: Relevance
“…Thus, it is unknown if dysferlin-deficiency impairs cardiac ion channel function, a potential pathophysiological mechanism in the dysferlinopathies. The following lines of evidence point to a potential regulatory effect of dysferlin on Ca v 1.2 channels: First, in skeletal muscle, dysferlin colocalizes with the L-type calcium channel [16,17], and muscle membrane repair requires an interplay between these two proteins [18]. Secondly, the dysferlin interaction partner AHNAK [19,20] associates with regulatory β-subunits of Ca v 1.2 channels [21,22], and thirdly, the α 2 δ 1 calcium channel subunit, which modulates the channel's function [23], is significantly downregulated in the dysferlin-deficient heart (NCBI GEO profile: http://www.ncbi.nlm.nih.gov/geoprofiles?term=GDS1247[ACCN]+cacna2d1, ref.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is unknown if dysferlin-deficiency impairs cardiac ion channel function, a potential pathophysiological mechanism in the dysferlinopathies. The following lines of evidence point to a potential regulatory effect of dysferlin on Ca v 1.2 channels: First, in skeletal muscle, dysferlin colocalizes with the L-type calcium channel [16,17], and muscle membrane repair requires an interplay between these two proteins [18]. Secondly, the dysferlin interaction partner AHNAK [19,20] associates with regulatory β-subunits of Ca v 1.2 channels [21,22], and thirdly, the α 2 δ 1 calcium channel subunit, which modulates the channel's function [23], is significantly downregulated in the dysferlin-deficient heart (NCBI GEO profile: http://www.ncbi.nlm.nih.gov/geoprofiles?term=GDS1247[ACCN]+cacna2d1, ref.…”
Section: Introductionmentioning
confidence: 99%
“…In similar examples, it was reported that dysferlin was also fragmented by calpain into ''mini-dysferlin'' and acted as a valid molecule for membrane repair [34]. We realized that it will be important in future analyses to test whether the culture medium after contraction possesses this healing effect.…”
Section: Discussionmentioning
confidence: 74%
“…Indeed, fusion of dysferlin-rich vesicles to the plasmalemma necessitates prior decoration of the injury site by MG53. However, dysferlin recruitment to the membrane have been shown to occur before that of MG53-rich vesicle [43,114,119]. This is particularly puzzling, since dysferlin is also enriched in the sarcolemma and transverse tubules of uninjured muscle fibers [120].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Dysferlin-mediated fusion also necessitates processing of dysferlin by calpains into minidysferlinC72 [43,119,126]. Dysferlin processing do not involve the muscle-specific calpain-3, but rather µ-calpain and m-calpain, as Caspn3-null mice do not show signs of loss of sarcolemma resealing after needle scratch or laser damage [127].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation